SOME IMMUNOLOGICAL INDICATORS IN CERVICAL PATHOLOGY ASSOCIATED WITH PAPILLOMAVIRUS INFECTION - A. A. Savchenko; V. B. Tskhay; D. Yu. Kruglova; A. G. Borisov (Медицинская иммунология)
Abstract. To study immunological indices and functional activity of neutrophils in women with human papillomavirus infection (HPV), as well as their dependence on severity of cervical morphological alterations, we examined sixty-seven female patients in their reproductive age. It was found that, regardless of severity of pathological changes in uterine cervix, the women with HPV infection show decreased numbers of NK cells and CD4+ lymphocytes in peripheral blood, along with increased contents of gd T cells. In cases of combined sub-clinical infection with leukoplakia and endocervicosis, more severe disorders of cellular immunity were detectable than in CIN I and CIN II. It is assumed, that initial neoplastic processes with HPV background are accompanied by a more pronounced immune response. Meanwhile, functional activity of neutrophilic granulocytes varies in an inverse manner, being, generally, increased in common HPV infection, followed by most significant changes in CIN I and CIN II.